(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
The article systematically breaks down the British education system into various stages, beginning with early years education and progressing through primary, secondary, further, and higher education. Each stage is elaborated upon, shedding light on the age groups, educational objectives, and key assessments,such as GCSEs and A-Levels, that shape students’ academic paths.